TAFSĪR AL-QUR’ĀN AL-‘AẒĪM: INTERTEKS DAN ORTODOKSI DALAM PENAFSIRAN RADEN PENGULU TAFSIR ANOM V - Arif Junaidi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractThis paper is aimed at answering two basic questions; how does the Qur’anic interpretation of Raden Pengulu Tafsir Anom as a text relate to the previous texts and how the trend of orthodoxy representing within the text. This paper has come into two pivotal findings; firstly, the work of interpretation has created meanings by referring to other texts or we call it an inter-text approach, both written text or unwritten text created by cultural and social settings surrounding the writer. However, the work of interpretation does not fully use all production models of meaning namely permutations, opposition and transformation. The models which are used just permutation and transformation, the way of producing meaning by changing the sentence structure to become various explanations which are easier to understand. The choice is only on these two models implicating to a very limited meaning production. Secondly, the trend of Islamic orthodoxy represented by the Tafsir Anom’s work of interpretation which can be seen from two different levels. Firstly, the level of thought as can be seen in his interpretations, especially the theological thinking. In terms of God as the creator and human as His creature, Tafsir Anom explains that God obliges and requires His creature to worship to Him without involving any intermediary subjects in any form. Secondly, level of reference as the source of his interpretation sources. Referring to the Islamic interpretations had been done by posititioning them as a system of rule. Positioning the referred text or hipogram text as the guidance has particular logical consequences, i.e. logical consequences of orthodoxy, since the referred texts are  orthodox texts.Key words: Intertext, Orthodoxy, Tafsir